HUBUNGAN KEPATUHAN ANTENATAL CARE DENGAN TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS PARUGA KOTA BIMA TAHUN 2025 - Nurfadilah; Bayti Jannah; Tri Yubiah (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2025)
The maternal mortality rate (MMR) in 2022 was 98 per 100,000 live births, while in 2023 it was 177 per 100,000 live births. In 2024, the maternal mortality rate (MMR) was 86 per 100,000 live births. ANC check-ups are decreasing every year.This research is a quantitative research with an observational analytical design and uses a cross-sectional approach which was carried out in September 2025. The population of pregnant women in the third trimester was 35 pregnant women, with a research sample of 35 pregnant women in the third trimester and using a total sampling technique. Data analysis used the Chi-Square test to test the relationship hypothesis.The results of statistical analysis showed that from a total of 35 respondents, as many as 26 respondents (74.3%) showed compliance in conducting ANC visits, while 9 other pregnant women respondents (25.7%) did not comply in conducting ANC visits as recommended. Then those who experienced anxiety were 28 respondents (80%), while 7 other respondents (20%) did not experience anxiety. Based on the Chi-square test, p Value> 0.153 and p value> 0.05 were obtained, indicating that there was no statistically significant relationship between Antenatal Care Compliance and Anxiety in Pregnant Women in the Third Trimester.